Определение изменения потребительских предпочтений алкогольных напитков на региональном уровне (Путеводитель предпринимателя)
In the work an analysis of the Russian alcohol market has been carried out. For forecasting of consumer preferences a market model on the basis of dynamic clusterization has been. By means of the model an analysis of the Smolensk alcohol market has been carried out.